Statin treatment, phenotypic frailty and mortality among community-dwelling octogenarian men: the HBS cohort. (22nd November 2019) - Luotola, Kari; Jyväkorpi, Satu; Urtamo, Annele; Pitkälä, Kaisu H; Kivimäki, Mika; Strandberg, Timo E
Abstract: Background: statin treatment has increased also among people aged 80 years and over, but adverse effects potentially promoting frailty and loss of resilience are frequent concerns. Methods: in the Helsinki Businessmen Study, men born in 1919–34 (original n = 3, 490) have been followed up since the 1960s. In 2011, a random subcohort of home-living survivors ( n = 525) was assessed using questionnaires and clinical (including identification of phenotypic frailty) and laboratory examinations. A 7-year mortality follow-up ensued. Results: we compared 259 current statin users (median age 82 years, interquartile range 80–85 years) with 266 non-users (83; 80–86 years). Statin users had significantly more multimorbidity than non-users (prevalencies 72.1% and 50.4%, respectively, P < 0.0001) and worse glucose status than non-users (prevalencies of diabetes 19.0% and 9.4%, respectively, P = 0.0008). However, there was no difference in phenotypic frailty (10.7% versus 11.2%, P = 0.27), and statin users had higher plasma prealbumin level than non-users (mean levels 257.9 and 246.3 mg/L, respectively, P = 0.034 adjusted for age, body mass index and C-reactive protein) implying better nutritional status. Despite morbidity difference, age-adjusted 7-year mortality was not different between the two groups (98 and 103 men among users and non-users of statins, respectively, hazard ratio 0.96, 95% confidence interval 0.72–1.30). Conclusions: our study suggests that male octogenarian statin users preserved resilience and survival despite multimorbidity, and this may be associated with better nutritional status among statin users.